Assessing the quality of life in a rural Thai province: A case study - Preeputtarat, Woottichai; Sutthisai, Watcharin; Kietjareon, Somkiet; Saiyaros, Ratchanida; Boonruan, Sathitkoon (Edelweiss Applied Science and Technology, 2024)
This study investigates the impact of personal characteristics (PER), personal environment (PEV), individual factors (INF), and urban development (DEV) on the quality of life (QoL) in the northeastern (Isan) region of Thailand, specifically focusing on Roi Et Province. The research employs a quantitative approach using stratified random sampling to select a sample of 400 individuals from a population of just over 1 million residents. Data analysis was conducted using LISREL 9.1 for confirmatory factor analysis (CFA) and structural equation modeling (SEM) to explore the relationships between the variables. The results reveal significant positive relationships between the studied variables and their influence on public services. Personal characteristics showed a moderate positive effect on QoL, highlighting the importance of gender and community relationships. The personal environment significantly impacted QoL, emphasizing the role of supportive living conditions. Individual factors were crucial for QoL, indicating the significance of societal roles and personal well-being. Urban development directly influenced QoL, suggesting that well-planned infrastructure enhances residents' QoL. These findings align with the Social Determinants of Health framework and New Urbanism theory. This research underscores the multifaceted nature of QoL determinants in rural settings, demonstrating that both individual and environmental factors contribute to residents' well-being. The study provides valuable insights for policymakers and urban planners, suggesting that enhancing personal and environmental factors, alongside strategic urban development, can significantly improve the quality of life in rural areas.